Factors affecting eco-friendly purchase intention: subjective norms and ecological consciousness as moderators - Dikdik Harjadi; Ardi Gunardi (Cogent Business & Management, 2022)
The aim of the study is to examine the influence of altruistic values, egoistic values, and perceived consumer effectiveness on eco-friendly purchase intention, with moderating effect of subjective norms and ecological consciousness using the stimulus organism response paradigm. The primary data were collected from 491 Indonesian customers using snowball sampling, and the data were analyzed using a structural equation model. The results revealed that altruistic, egoistic, and perceived consumer effectiveness had a significant impact on consumer attitude and perceived behaviour control. Similarly, customer attitude and perceived behaviour control influenced eco-friendly purchase intention. Subjective norms showed positive moderation between attitude, perceived behaviour control, and purchase intention; similarly, eco-friendly consciousness had a positive connection between attitude and purchase intention but not between perceived behaviour control and purchase intention. The study's results will help green marketers devise new strategies for attracting and increasing sales volume in Indonesia's growing markets.
Keywords: 650; altruistic value; eco-friendly purchase intention; ecological consciousness; egoistic value; perceived consumer effectiveness; subjective norms